Circadian variation of tissue plasminogen activator and its inhibitor, von Willebrand factor antigen, and prostacyclin stimulating factor in men with ischaemic heart disease. Issue 2 (February 1993) - Bridges, A B; McLaren, M; Scott, N A; Pringle, T H; McNeill, G P; Belch, J J
Abstract : OBJECTIVES--To determine whether plasma concentrations of tissue plasminogen activator antigen, von Willebrand factor antigen, and prostacyclin stimulating factor and plasminogen activator inhibitor activity show circadian variation in men with ischaemic heart disease. DESIGN--Blood samples were obtained every four hours for 24 hours from 10 men with ischaemic heart disease. The men were ambulant from 08:10 until 00:00 when they went to bed and they remained in bed until 08:00 the following morning. PATIENTS--Ten men with positive diagnostic exercise tolerance tests with no significant past history, who were not regularly taking any medical treatment except for glyceryl trinitrate. RESULTS--There was significant circadian variation in plasminogen activator inhibitor activity (p = 0.001) (peak value 04:00 and trough value 20:00), but not in plasma concentrations of tissue plasminogen activator antigen, von Willebrand factor, or prostacyclin stimulating factor. CONCLUSION--Men with ischaemic heart disease showed a significant circadian variation in fibrinolysis. The combination of peak values of plasminogen activator inhibitor activity and failure of plasma concentrations of tissue plasminogen activator antigen to increase in the early morning must predispose to thrombosis at this time. The circadian variation in fibrinolysis may contribute to the increased incidence of myocardial infarction in the morning.